Using of TLR2 and TLR4 as Biomarker for Detection the Severity of Sepsis - Younis , Farah Qahtan; Alwan, Ali Hussien; Zaki, Neihaya Hekmit (International Journal of Psychosocial Rehabilitation, 2020)
Our study has been aimed to find the relation between the expression of toll-like receptors 2, 4, level of TNF-α, IL-10 and soluble HLA-DR with the severity bacterial septic syndrome in Iraqi patients. The quantitative real-time PCR technique has been used for measure TLR2 and TLR4 gene expression in whole blood, and ELISA technique has been used for detection of cytokines TNF-α, IL-10 and soluble HLA-DR from 75 septic syndrome cases (nineteen of patients showed symptoms of systemic inflammatory response syndrome (SIRS); twenty eight patients have sepsis, seventeen patients suffered from severe sepsis and eleven patients have septic shock) and 55 healthy controls (HC). TLR2 and TLR4 mRNA expression were higher significantly in the all patients (P< 0.05), TNF-α, IL-10 and sHLA-DR serum levels were significantly elevated in the serum of patients with septic syndrome compared with controls (P<0.05) except the level of HLA-DR in SIRS patients there were no differences with a healthy control group. Also the results have been shown, there are significant differences in TLR2 and TLR4 between the stages of septic syndrome and also a positive correlation between TLR 4 and concentration of sHLA-DR. According to the results of our study, we can conclude the possibility of using TLR 2 and TLR 4 expression to determine the severity of sepsis as diagnostic biomarker.